Trends in oral health in young people in the Netherlands over the past 20 years: a study in a changing context. Issue 2 (23rd September 2013) - Schuller, A.A.; van, P.; Poorterman, J.H.G.
Abstract Objectives From 1 January 2006, the distinction between the health insurance fund and private insurance was abolished and a basic insurance package was agreed for everyone in the Netherlands. Dental treatment for young people below the age of 18 is reimbursed under the terms of this basic package. Dental treatment for adults is not covered in this basic insurance package. Basic principles for nonreimbursing dental care for adults were that any health and financial risks for individual citizens in the future should be acceptable for them with the corollary that the oral health of young adults when they make the switch ‐ from collectively financed care to care to be paid for individually ‐ should be at such a level that the needed oral health care is affordable. To meet this requirement, it is important to have knowledge of the prevalence of oral diseases and trends in oral health in young people from a public health perspective. The aim of this article is to describe trends in caries experience in young people in the Netherlands from 1990 to 2009, taking into account the challenge in methodology concerning this changing social context. Methods To describe caries experience in young people, a repeated cross‐sectional study design was used. The study consisted of a clinical oral examination and a questionnaire survey. Data were sampled from 8, 14 and 20‐year‐olds in 1990 and 1996, and 9, 15 and 21‐year‐olds in 2003 and 2009, living in Alphen a/d Rijn, Gouda, Breda and 's‐Hertogenbosch. The DMF index was used for describing caries experience. The trends were studied separately in high and low socioeconomic status (SES) groups. SES was operationalized as the dichotomous variable of educational level of the mother or the adolescent. Multiple imputation was applied to predict the DMFS for missing ages for certain years, which made it possible to test the trends. Linear and logistic regression analyses were used to study the trends through the years. Results This study showed, according to different age‐ and SES groups, either declines or no statistically significant changes in caries experience over the last two decades. Conclusions No deterioration was shown. However, there is still room for further improvement in oral health in children. Dental professionals and politicians should develop a vision on to what extent caries experience is acceptable in a public health perspective in young people.